Seed exploration and conservation in Ciremai Mountain National Park and Kerinci Seblat National Park. Issue 1 (February 2020) - Wanda, I F; Oksari, A A; Sahromi,; Mimin,; latifah, D
Abstract: Seed storage at a seed bank facility is one of the ex-situ bioresources conservation strategies in the world's Botanical Gardens. Enrichment of species for seed banks is done through exploration in various forest areas. The exploration and conservation of seeds have been done in Ciremai Mountain National Park (CMNP) on November 7-16 th, 2016 and Kerinci Seblat National Park (KSNP) on April 11-20 th, 2017. This research aims to search and collect plant seeds and to know the diversity of species from fruiting plants and seeds. Furthermore, this exploration also aims to study a biological seed that support conservation efforts for these plants. Research used an exploratory method at each location. The recording of ecological data includes habitat, altitude, soil pH, soil moisture, and air temperature. This study obtained thirty-two (32) collection numbers in the CMNP area consisted of 20 families and 28 genera; and thirty-three (33) collection numbers consisted of 21 families and 31 genera in the KSNP area. Most of the seeds found are orthodox seeds that can be stored for a relatively long time.